2019
DOI: 10.1103/physrevb.100.064415
|View full text |Cite
|
Sign up to set email alerts
|

(LaCoO3)n/(SrCoO2.5)

Abstract: Ferromagnetic insulators have great potential for spintronic applications. For such applications, it is essential to find materials with a robust and controllable ferromagnetic insulating phase. However, because ferromagnetism in functional transition metal oxides is usually coupled to metallicity, ferromagnetic insulators are very rare and independent control of their magnetic and electrical properties is difficult. In this study, the electrical, magnetic, and optical properties of (LaCoO 3) n /(SrCoO 2.5) n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Moreover, strain gradient originating from gradual distribution of oxygen vacancies results in flexoelectricity and potentially enhances piezoelectricity in SrMnO 3 /(LaAlO 3 ) 0.3 (Sr 2 AlTaO 6 ) 0.7 . In summary, in the past several years, more and more studies have shown that by modulating oxygen vacancy behaviors, specific properties of oxide films could be enhanced or fabricated. …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, strain gradient originating from gradual distribution of oxygen vacancies results in flexoelectricity and potentially enhances piezoelectricity in SrMnO 3 /(LaAlO 3 ) 0.3 (Sr 2 AlTaO 6 ) 0.7 . In summary, in the past several years, more and more studies have shown that by modulating oxygen vacancy behaviors, specific properties of oxide films could be enhanced or fabricated. …”
Section: Introductionmentioning
confidence: 99%
“…Advances in atomic-scale functional oxide film epitaxial growth have made it possible to control the structure and properties of materials through heterogeneous interfaces. The broken symmetry brought by the interface has led to the discovery of a large number of abnormal physical phenomena, such as two-dimensional electron gas, interface superconductivity, fractional quantum hall effect, , topological insulator, and magnetoelectric coupling. , The coupling between different degrees of freedom on both sides of the interface, such as spin, orbit, charge, and lattice, produces a lot of abnormal physical properties on the interface. Interfaces can also affect the structure and properties away from the interface. For example, some studies discovered the interaction between ferroelectric domain walls and defects at the interfaces is induced by different interface conditions …”
Section: Introductionmentioning
confidence: 99%
“…Recently, electrochemical gating is widely used as a new method for the control of functional materials, for example, Lu et al have shown that by changing the voltage, they can control tristate phase transformation and oxygen vacancy ordering during ionic liquid gating, Parkin and co-workers discovered that oxygen vacancy ordering can be controlled via ionic liquid gating . For the control of oxygen vacancy ordering in LaSrCoO 3– x , LaCoO 3– x (LCO), SrCoO 3– x , and so forth, researchers are showing more and more interest. ,,, We propose that oxygen vacancy ordering can be controlled by designing different interface boundary conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Ferromagnetic-Insulators (FM-Is) are opening new avenues for next generation spintronic devices and spin wave information processing applications [1,2,3,4,5,6]. The exchange field proximity effect from FM state and negligible effective charge current due to I state, make FM-I useful as spin filter [7], quantum topological system [8], and dissipationless medium [9].…”
Section: Introductionmentioning
confidence: 99%
“…The exchange field proximity effect from FM state and negligible effective charge current due to I state, make FM-I useful as spin filter [7], quantum topological system [8], and dissipationless medium [9]. Achieving control over the ground state in FM-Is can further extend the feasibility of these systems in aforementioned technological perspectives [3].…”
Section: Introductionmentioning
confidence: 99%